Part‐night lighting: implications for bat conservation. (18th March 2015) - Day, J.; Baker, J.; Schofield, H.; Mathews, F.; Gaston, K. J.
Abstract: Artificial nighttime lighting has many effects on biodiversity. A proposed environmental management option, primarily to save energy, is to alter the duration of night lighting. Using the greater horseshoe bat R hinolophus ferrumequinum as an example of a photophobic species, we explored roadside behaviour patterns throughout the night to assess the potential impact of part‐night lighting. We found a large primary peak in activity 1 h after sunset, followed by a smaller secondary peak before sunrise. Simulated part‐night lighting scenarios reveal that to capture a large proportion of bat activity, streetlights should be switched off before midnight. Current proposed uses of part‐night lighting are unlikely to capture natural peaks in activity for nocturnal species.